Effect of fluoride-releasing adhesive systems in control of dental enamel hardness subjected to acid challenge - Sahyon, Henrico Badaoui Strazzi; Guedes, Ana Paula Albuquerque; Godas, André Gustavo de Lima; Suzuki, Thaís Yumi Umeda; Briso, André Luiz Fraga; dos Santos, Paulo Henrique (ARCHIVES OF HEALTH INVESTIGATION, 2017)
Purpose: To evaluate the effect of pH cycling with erosive solutions on the Knoop hardness of enamel restored with different fluoride-releasing materials. Methods: Eighteen selected bovine teeth were used and divided into 3 groups (n = 6) according to the restorative material used (Single Bond 2, One Up Bond F and Clearfil SE Protect). Three slices of each restored tooth were subjected to erosive pH cycling in acidic solutions (deionized water, citric acid and hydrochloric acid), with alternate phases of demineralization and remineralization. The microhardness recorded before and after erosive pH cycling was used to determine changes in the enamel. Results: Acidic solutions were able to change the hardness of enamel. After immersion in citric acid, the enamel restored with Clearfil SE Protect showed lesser mineral loss than the enamel restored with other materials at a distance of 30μm. There was an increase in the mineral loss after cycling with hydrochloric acid, compared to deionized water. In the distance of 70µm from adhesive interface, the enamel restored with Single Bond 2 showed greater mineral loss after immersion in citric acid. Conclusions: The fluoride present in Clearfil SE Protect adhesive system was able to protect the dental enamel against erosion process. Descriptors: Tooth Demineralization; Dental Enamel; Sodium Fluoride.